Pengaruh Efikasi Diri terhadap Kesejahteraan Subjektif yang Dimediasi oleh Resiliensi pada Siswa SMA - Erni, Yuli; Dewi, Salamiah Sari; Surbakti, Amanah (Universitas Muhammadiyah Metro, 2025)
Adolescence is a stage that is vulnerable to psychological pressure, making it crucial to identify internal factors that can enhance subjective well-being. This study aims to examine the influence of self-efficacy on subjective well-being, mediated by resilience in senior high school students. A quantitative approach was employed. Participants consisted of 449 students selected through cluster random sampling. The instruments used included the General Self-Efficacy Scale (GSES-12), the Connor-Davidson Resilience Scale (CD-RISC), and the Brief Adolescent Subjective Well-Being in School Scale (BASWBSS). Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via SmartPLS software. The results revealed that self-efficacy had a positive and significant effect on both resilience and subjective well-being. Resilience also positively influenced subjective well-being and significantly mediated the relationship between self-efficacy and subjective well-being. These findings highlight that enhancing students’ self-efficacy can strengthen their resilience, which ultimately contributes to improved subjective well-being. The implications of this study underscore the importance of fostering self-efficacy and resilience as key components in efforts to promote psychological well-being among high school students.